The Influence of Work Motivation and Physical Work Environment on Employee Performance at PT. Arkadia Sinergi Indonesia - Salamah, Siti; Prasetiyani, Desi (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2024)
The purpose of this research is to determine the positive and significant influence of work motivation variables and the physical environment simultaneously on employee performance at PT Arkadia Sinergi Indonesia. This research method uses quantitative methods with a sample size of 70 respondents, the data analysis technique used is: validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, simple correlation coefficient test, multiple correlation coefficient test, coefficient of determination analysis test, t test and f test. Based on the results of the t test, it was found that the calculated t value was 2.048, which exceeded the critical value of 1.668, and the significance value for the work motivation variable (X1) was 0.004, smaller than the probability set at 0.05 (0.004<0.05). Thus, it can be concluded that the work motivation variable (X1) has a positive and significant influence on employee performance (Y) at PT. Arkadia Sinergi Indonesia. Based on the results of the t test, it was found that the calculated t value was 3.562, which exceeded the critical value of 1.168, and the significance value for the physical work environment variable (X2) was 0.001, smaller than the probability set at 0.05 (0.001<0.05). Thus, it can be concluded that the physical work environment variable (X2) has a positive and significant influence on employee performance (Y) at PT. Arkadia Sinergi Indonesia. Based on the F test results, the calculated f value was 6.257, which exceeds the critical value of 3.134, and the significance value is 0.003, which is smaller than the significance level of 0.05. Therefore, it can be concluded that the work motivation variables (X1) and the physical work environment (X2) together have a positive and significant influence on employee performance (Y) at PT Arkadia Sinergi Indonesia